Ascertaining the legal effectiveness of the person with disabilities act 2008 (pwda) in facilitating equal rights to employment o disabled person in Malaysia / Nor Fithryiah Che Abd Rani... [et al.] - Che Abd Rani, Nor Fithryiah; Muhmmed Ayub, Noorhani; Musa, Nur Hidayah; Jamal, Nurazean (2009)
This research is set up to study on the effectiveness of the person with Disabilities Act 2008 in facilitating equal rights to employment to disabled people in Malaysia by adopting qualitative type of research. According to the interviews and research that have been conducted, PWDA would appear to have vital implications towards disabled people. The act inutVentirely is not satisfactory and there is definitely more room for improvement in the PWDA especially in the area of employment. Compared to the laws in United Kingdom and Australia, the PWDA is purely an administrative act and "toothless" as there are no punitive measures for non compliance or acts of discrimination. Thus this act has not yet shows how effective it is in protecting the rights of disabled people on employment.